AP-ASD1 : An Indonesian Desktop-based Educational Tool for Basic Data Structure Course - Lucky Christiawan; Oscar Karnalim (Maranatha University Press, 2016)
Although there are so many avalaible data structure educational tools, it is quite difficult to find a suitable tool to aid students for learning certain course [1]. Several major impediments in determining the tool are teaching preferences, language barrier, confusing terminologies, internet dependency, various degree of material difficulty, and other environment aspects. In this research, a data structure educational tool called AP-ASD1 is developed based on basic algorithm and data structure course (ASD 1). Since AP-ASD1 is developed following course materials and not vice versa, this educational tool is guaranteed to fit in our needs. The feasibility of AP-ASD1 is evaluated based on two factors which are functionality correctness and survey. All features are correctly functioned and yield expected output whereas survey yields fairly good result (84,305% achievement rate). Based on our survey, AP-ASD1 meets eligibility standard and its features are also successfully integrated. Survey also concludes that this application is also quite effective as a supportive tool for learning basic data structure.